Emulsion electrospinning of lemongrass essential Oil-Loaded Ferula haussknechtii gum/ Polyethylene oxide as bioactive coating - Saeedeh Jafari; Abdollah Hematian Sourki; Safoora Pashangeh (Food Hydrocolloids for Health)
This study aimed to develop a novel, degradable antimicrobial bioactive coating by combining Ferula haussknechtii gum and polyethylene oxide with lemongrass essential oil (LGEO) using the emulsion electrospinning technique. The LGEO emulsion in the F. haussknechtii gum/polyethylene oxide solution was prepared via ultrasonic method, and its physicochemical properties, including pH, electrical conductivity, density, and apparent viscosity, were systematically evaluated. The microstructural morphology of the electrospun coating was analyzed using scanning electron microscopy (SEM). The antimicrobial properties and antioxidant potential of the active electrospun coating were also assessed. The resulting electrospun fibers had an average diameter of 0.56 μm and contained over 36 bioactive compounds, exhibiting radical scavenging activity of approximately 74.51 %. The LGEO was incorporated into the bioactive coating at concentrations of 3, 6, and 9 % (v/v). The antimicrobial efficacy of the electrospun coating was tested against Gram-positive Gram-negative, and Aspergillus niger. The highest antimicrobial activity was observed with the electrospun coating containing 9 % LGEO. The results revealed that increasing the LGEO concentration in the emulsion resulted in decreased pH, apparent viscosity, and density, while electrical conductivity increased. SEM analysis confirmed the formation of uniform, bead-free electrospun fibers across all LGEO concentrations. FTIR analysis validated the successful incorporation of emulsified LGEO into the electrospun fibers. These findings demonstrate that the inclusion of LGEO in bioactive edible coatings can significantly enhance antimicrobial protection, particularly for minimally processed foods, while potentially extending shelf life by reducing microbial contamination.